If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 149 + -5x = 22x + 23 Reorder the terms: 149 + -5x = 23 + 22x Solving 149 + -5x = 23 + 22x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22x' to each side of the equation. 149 + -5x + -22x = 23 + 22x + -22x Combine like terms: -5x + -22x = -27x 149 + -27x = 23 + 22x + -22x Combine like terms: 22x + -22x = 0 149 + -27x = 23 + 0 149 + -27x = 23 Add '-149' to each side of the equation. 149 + -149 + -27x = 23 + -149 Combine like terms: 149 + -149 = 0 0 + -27x = 23 + -149 -27x = 23 + -149 Combine like terms: 23 + -149 = -126 -27x = -126 Divide each side by '-27'. x = 4.666666667 Simplifying x = 4.666666667
| 5x+13=-137-10x | | 7-5(x-2)=5-3(x+3) | | 11-9x=29-16x | | -9+2z=9z+12 | | 2(x-1)-3(2-x)+4(1-x)=0 | | -23-4x=9-8x | | -134-7x=8x+16 | | -5(k+5)+5k= | | 5(b-4)+25= | | 0=3(2-3x)-7(x-3) | | 10+2(4y+3)= | | 3x-2(12-x)=4(2x-3)+3(x+1) | | 6-5c=-14 | | 6(1-x)+4=3(2-x)-4 | | 4x+10=90-6 | | 40-2(x+1)=90 | | 4k+6=6k-2 | | 6(2x+1)+7=9x+1 | | 6x+9=-119-10x | | 3(7x-1)+8(3-2x)=1 | | -2*5= | | 5(2x+3)-3(x+1)=5 | | 8(x-2)-2(2x-1)=2x+1 | | -2(5r+3)= | | 5a+30b=25 | | 5(3x-4)=8x+1 | | 6a-4=8 | | 3(10a)= | | 2x-3(2-x)=4 | | 4(x+3)-2=2 | | 3(x+1)+2(2x+7)=3 | | 5(f-12)=9+5f |